Spatially fractionated radiotherapy (GRID) using helical tomotherapy. (8th January 2016) - Zhang, Xin; Penagaricano, Jose; Yan, Yulong; Liang, Xiaoying; Morrill, Steven; Griffin, Robert J.; Corry, Peter; Ratanatharathorn, Vaneerat
Abstract : Spatially fractionated radiotherapy (GRID) was designed to treat large tumors while sparing skin, and it is usually delivered with a linear accelerator using a commercially available block or multileaf collimator (LINAC‐GRID). For deep‐seated (skin to tumor distance ( > 8   cm ) ) tumors, it is always a challenge to achieve adequate tumor dose coverage. A novel method to perform GRID treatment using helical tomotherapy (HT‐GRID) was developed at our institution. Our approach allows treating patients by generating a patient‐specific virtual GRID block (software‐generated) and using IMRT technique to optimize the treatment plan. Here, we report our initial clinical experience using HT‐GRID, and dosimetric comparison results between HT‐GRID and LINAC‐GRID. This study evaluates 10 previously treated patients who had deep‐seated bulky tumors with complex geometries. Five of these patients were treated with HT‐GRID and replanned with LINAC‐GRID for comparison. Similarly, five other patients were treated with LINAC‐GRID and replanned with HT‐GRID for comparison. The prescription was set such that the maximum dose to the GTV is 20 Gy in a single fraction. Dosimetric parameters compared included: mean GTV dose ( D GTV mean ), GTV dose inhomogeneity (valley‐to‐peak dose ratio (VPR)), normal tissue doses ( D N mean ), and other organs‐at‐risk (OARs) doses. In addition, equivalent uniform doses (EUD) for both GTV and normal tissue were evaluated. In summary, HT‐GRID technique is patient‐specific, and allows adjustment of the GRID pattern to match different tumor sizes and shapes when they are deep‐seated and cannot be adequately treated with LINAC‐GRID. HT‐GRID delivers a higher D GTV mean, EUD, and VPR compared to LINAC‐GRID. HT‐GRID delivers a higher D N mean and lower EUD for normal tissue compared to LINAC‐GRID. HT‐GRID plans also have more options for tumors with complex anatomical relationships between the GTV and the avoidance OARs (abutment or close proximity). PACS numbers: 87.55.D, 87.55.de, 87.55.ne, 87.55.tg